Online Shopping Consumptive Behavior Of Teenagers In The Perspective Of Imam Al-Ghazali - M, Nurhikmah; Casmini (Jeksyah: Islamic Economics Journal, 2023)
This study discusses online shopping consumptive behavior using the literature review method, by collecting data from several documents in the form of books, articles and other literature relevant to the topics discussed. The results of this study indicate several factors that lead to consumptive online shopping behavior among adolescents, namely the flow of globalization, psychological development, peer influence, permissive parenting and family socio-economic levels, and low self-control. The consumption patterns that occur in online shopping consumptive behavior among adolescents in Al-Ghazali's perspective are very far from Islamic values ​​which aim to achieve falah and maslahah. Teenagers in fulfilling their needs only follow their desires without any consideration in the ownership of goods or the use of services that are goal oriented to their creation as servants and caliphs on earth. So that the online shopping consumptive behavior of teenagers is not in line with the principles of simplicity and the principles of moral ethics in Islam which lead to tabzir attitudes.